Comparative Analysis of Religious Education Systems: A Global Perspective - Marion Maddox; Robyn Ewing; Mark Hutchinson (Green Philosophy: International Journal of Religious Education and Philosophy, 2024)
This article offers a comparative analysis of religious education systems across different countries. It examines the approaches to religious education in diverse cultural and national contexts, assessing their effectiveness in promoting religious understanding, moral development, and social cohesion. The study provides recommendations for enhancing religious education based on international best practices.